Diarrheagenic Escherichia coli Associated with Acute Gastroenteritis in Children from Soriano, Uruguay. (24th October 2018) - Peirano, Vivian; Bianco, María Noel; Navarro, Armando; Schelotto, Felipe; Varela, Gustavo
Abstract : Introduction . Acute diarrheal disease still deserves worldwide attention due to its high morbidity and mortality, especially in developing countries. While etiologic determination is not mandatory for management of all individual cases, it is needed for generating useful epidemiologic knowledge. Diarrheagenic Escherichia coli (DEC) are relevant enteropathogens, and their investigation requires specific procedures to which resources and training should be dedicated in reference laboratories. Methodology . Following the hypothesis that enteric pathogens affecting children in towns located in the interior of Uruguay may be different from those found in Montevideo, we conducted a diagnostic survey on acute diarrheal disease in 83 children under 5 years of age from populations in the south of the country. Results . DEC pathotypes were the only bacterial pathogens found in diarrheal feces (20.48%), followed by rotavirus (14.45%) and enteric adenovirus (4.81%). Atypical EPEC (aEPEC) was the most frequent DEC pathotype identified, and unexpectedly, it was associated with bloody diarrheal cases. These patients were of concern and provided with early consultation, as were children who presented with vomiting, which occurred most frequently in rotavirus infections. aEPEC serotypes were diverse and different from those previously reported in Montevideo children within the same age group and different from serotypes identified in regional and international studies. Enteroinvasive (EIEC) O96 : H19, associated with large outbreaks in Europe, was also isolated from two patients. Antibiotic susceptibility of pathogenic bacteria identified in this study was higher than that observed in previous national studies, which had been mainly carried out in children from Montevideo. Conclusion . The reduced number of detected species, the marked prevalence of aEPEC, the scarce resistance traits, and the diverse range of serotypes in the virulent DEC identified in this study confirm that differences exist between enteropathogens affecting children from interior towns of Uruguay and those circulating among children in Montevideo.